2009
DOI: 10.1590/s0100-879x2009000700007
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection and its association with cervical dysplasia in Ecuadorian women attending a private cancer screening clinic

Abstract: Women living in Latin American countries bear a disproportionate burden of cervical cancer, a condition caused by infection with the human papillomavirus (HPV). We performed a study in Santa Elena, Guayas (currently Santa Elena Province), Ecuador, to determine how often HPV could be detected in women attending a private cancer screening clinic. Participants underwent a Pap test, and vaginal and cervical swabs were performed for HPV testing by the polymerase chain reaction (PCR). Each participant completed a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
1
22
1
7
Order By: Relevance
“…Studies in Ecuador found genotype 16 as the most common [32, 33, 35, 40], along with results of this investigation. The 18 genotype was not reported as the second most frequent, suggesting that genotypic variability by geographic region and sociodemographic factors had an effect, such that more research is necessary.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies in Ecuador found genotype 16 as the most common [32, 33, 35, 40], along with results of this investigation. The 18 genotype was not reported as the second most frequent, suggesting that genotypic variability by geographic region and sociodemographic factors had an effect, such that more research is necessary.…”
Section: Discussionsupporting
confidence: 80%
“…In the city of Cuenca, in a study of 500 women from the general population, the prevalence of 25.6% of HPV for both high and low risk [34] was similar to that reported in Santa Elena. Brown et al (2009) found [35] a prevalence of 24.2%. A higher prevalence of HPV with abnormal cytology studies indicates a relationship between the virus and malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…HPV detection and genotyping was performed using the Linear Array HPV Genotyping Test (LA-HPV) (Roche, Indianapolis, Indiana) as described previously [9-12]. The GH20/PC04 human β-globin target was co-amplified to determine sample adequacy.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed for specific HPV types using LA-HPV as previously described [Gravitt et al, 2000;Brown et al, 2005Brown et al, , 2009Shew et al, 2006;Fife et al, 2009]. A participant was considered HPV 16-positive if at least one of their samples contained HPV 16 DNA when tested with LA-HPV.…”
Section: Sample Collection and Hpv Genotypingmentioning
confidence: 99%